2022
DOI: 10.15252/embr.202052149
|View full text |Cite
|
Sign up to set email alerts
|

Constricted migration is associated with stable 3D genome structure differences in cancer cells

Abstract: To spread from a localized tumor, metastatic cancer cells must squeeze through constrictions that cause major nuclear deformations. Since chromosome structure affects nucleus stiffness, gene regulation, and DNA repair, here, we investigate the relationship between 3D genome structure and constricted migration in cancer cells. Using melanoma (A375) cells, we identify phenotypic differences in cells that have undergone multiple rounds of constricted migration. These cells display a stably higher migration effici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 94 publications
(116 reference statements)
6
18
0
Order By: Relevance
“…Surprisingly, increasing collagen concentrations in 2D culture did not affect heterochromatin levels ( Figure S6 C). Overall, these results suggest that when cells migrate through confined environments in 3D collagen matrices under MMPi, global heterochromatin levels do not show an increase, similar to previous reports ( Golloshi et al, 2022 ; Wang et al., 2018 ). At the same time, these findings point to the difficulty in interpreting results from 3D collagen matrices due to the pleiotropic effects of varying collagen concentrations.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Surprisingly, increasing collagen concentrations in 2D culture did not affect heterochromatin levels ( Figure S6 C). Overall, these results suggest that when cells migrate through confined environments in 3D collagen matrices under MMPi, global heterochromatin levels do not show an increase, similar to previous reports ( Golloshi et al, 2022 ; Wang et al., 2018 ). At the same time, these findings point to the difficulty in interpreting results from 3D collagen matrices due to the pleiotropic effects of varying collagen concentrations.…”
Section: Resultssupporting
confidence: 90%
“…Although time-lapse microscopy revealed formation of persistent GFP-HP1α enrichments in cells during and after nuclear transit through tight constrictions, indicating an active heterochromatin formation process, and the vast majority of cells that had passed through the constrictions had higher normalized H3K27me3 levels than observed in cells in the “before” population ( Figure 1 G), we cannot rule out the possibility that the observed increase in heterochromatin is a combination of both active induction and passive selection, as suggested by Golloshi et al. regarding the chromatin changes resulted from repeated transwell migration ( Golloshi et al, 2022 ). Taken together, these findings indicate that CMiH is distinct from heterochromatin associated with general migration initiation, which occurs before the onset of migration in 2D and 3D environments ( Gerlitz and Bustin, 2010 ; Segal et al., 2018 ).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…It can be assumed that the leading edge of the cell in open matrix creates a high forward stress on the cell, leading to strong deformation of the consecutively following nucleus inducing DNA damage. It is also suggested that such high nuclear stress states might induce epigenetic changes like changes in chromatin methylation and structure leading to the observed alterations in gene expression of the transmigrated cells as discussed also in the cited reports. , This hypothesis is supported by a recent report demonstrating that tumor cells and neutrophil-like cells exhibited changes in genomic variation upon migration through constraining pores, , which in turn enhanced their invasiveness and resistance to anoikis . Dynamic details of such a suggested process deserve further detailed investigations to verify our conclusions.…”
Section: Discussionsupporting
confidence: 84%